Idiopathic eruptive macular pigmentation - Trčko, Katarina (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
We presented the case of a 10-year-old girl with a six months history of disseminated asymptomatic, brown pigmented macules on the trunk and proximal parts of the extremities. The clinical picture, histological findings, and the course of disease were similar to those of idiopathic eruptive macular pigmentation. The cutaneous lesions gradually disappeared over the next two years without any treatment, and no relapse occurred. The knowledge of this disease is important in order to avoid unnecessary treatment as spontaneous resolution of the lesions may be expected within months or a few years. The spontaneous regression without any treatment is an additional diagnostic criterion.
Keywords: Child; dermatologija; kožne bolezni; motnje; Motnje pigmentacije; Otrok; pigmentacija; Pigmentation disorders